The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/nplants.2017.119
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Acetate-mediated novel survival strategy against drought in plants

Abstract: The Supplementary Information files originally published with this Letter were not the intended final versions. The Supplementary Information PDF and Supplementary Tables 3, 5 and 6 have now been updated to fix a number of cosmetic problems. No data have been affected and there have been no changes in meaning.© 2 0 1 7 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It has been previously demonstrated that TCAs are upregulated during the BABA-induced priming phase, respect to the Pst Rpt2-induced resistance ( Pastor et al, 2014 ). Therefore, the present study aimed to ask whether these compounds can also act as defense and/or priming inducers, as previously demonstrated for other acidic chemical signals such as azelaic acid, pipecolic acid and recently acetic acid ( Jung et al, 2009 ; Návarová et al, 2012 ; Kim et al, 2017 ). To test the defense inducing capacity of carboxylic acids, citrate and fumarate were chosen.…”
Section: Resultsmentioning
confidence: 94%
“…It has been previously demonstrated that TCAs are upregulated during the BABA-induced priming phase, respect to the Pst Rpt2-induced resistance ( Pastor et al, 2014 ). Therefore, the present study aimed to ask whether these compounds can also act as defense and/or priming inducers, as previously demonstrated for other acidic chemical signals such as azelaic acid, pipecolic acid and recently acetic acid ( Jung et al, 2009 ; Návarová et al, 2012 ; Kim et al, 2017 ). To test the defense inducing capacity of carboxylic acids, citrate and fumarate were chosen.…”
Section: Resultsmentioning
confidence: 94%
“…In Arabidopsis , members of the RPD3/HDA1 family were found to interact with various proteins involved in plant stress responses and regulate gene expression through histone deacetylation ( Figure 1 ). HDA6 is involved in drought stress tolerance by regulating gene expression in the acetate biosynthesis pathway ( Kim et al, 2017 ). HDA6 also regulates the jasmonate (JA) associated stress response by interacting with COI1 and JAZ1, the key regulators of JA signaling ( Devoto et al, 2002 ; Zhu et al, 2011 ).…”
Section: Functions Of Hdacs In Salt and Drought Stress Responses In mentioning
confidence: 99%
“…In Arabidopsis, HDACs play an important role in the response to different stresses, as well as in plant development [18,[25][26][27]. Arabidopsis HDA6 is involved in drought stress tolerance [28] and regulates the jasmonate-associated stress response [29,30]. The Athda9 mutant showed enhanced tolerance to salt and drought stress, indicating that HDA9 may act as a negative repressor of the plant's stress response [31][32][33].…”
Section: Introductionmentioning
confidence: 99%